The fossil episode - John Hassler; Hans-Werner Sinn (Center for Economic Studies and ifo Institute (CESifo), 2012)
We build a two-sector dynamic general equilibrium model with one-sided substitutability between fossil carbon and biocarbon. One shock only, the discovery of the technology to use fossil fuels, leads to a transition from an initial pre-industrial phase to three following phases: a pure fossil carbon phase, a mixed fossil and biocarbon phase and an absorbing biocarbon phase. The increased competition for biocarbon during phase 3 and 4 leads to increasing food prices. We provide closed form expressions for this price increase. Our calibration leads to a price increase of 40% if capital and labor are allowed to move to the biocarbon sector. Otherwise, the price increase is much higher. We also use the model to analyze the consequences of restrictions on using biocarbon as fuel. We show that such restrictions can lead to a substantially slower global warming due to an endogenous slowdown of fossil fuel extraction.
Keywords: Q54; Q32; O41; 330; hotelling rule; fossil carbon; biocarbon; transition phases; oil price; food price; global warming